Flame retardant anti-skid sole and manufacturing process thereof
By using chlorinated polyethylene, ethylene-vinyl acetate copolymer and silicone rubber, composite foaming and adding fillers, the problems of degradation of anti-slip performance and lack of flame retardant performance in humid environments are solved, and the problem of existing sole materials is achieved. Excellent anti-slip and flame retardant properties.
Patent Information
- Application Number
- CN202410272113.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-03-11
AI Technical Summary
The existing sole materials have reduced anti-slip performance in wet ground environments and lack flame retardant properties.
Chlorinated polyethylene, ethylene-vinyl acetate copolymer and silicone rubber are used as rubber materials to form uniform bubble cells, increase fillers such as porous silicon powder and zinc oxide, and improve the hydrophilicity of the sole material through surface oxidation treatment.
The anti-slip performance of the sole material is improved, especially in humid environments, and its flame retardant properties are enhanced, forming a flame-retardant carbon layer to block heat and substances.
Smart Images

Figure BDA0004734628160000131 
Figure BDA0004734628160000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sole materials, in particular to a flame retardant anti-skid sole and a manufacturing process thereof. Background Art
[0002] When people walk, friction is generated between the sole and the ground. The anti-skid performance of the sole refers to the grip of the sole on the ground under the action of this friction. It is an important indicator for considering the safety performance of shoes. It is mainly affected by factors such as sole material, sole pattern, contact area, sole hardness, and humidity. The sole material is one of the most critical factors in the anti-skid performance of the sole. Common sole materials include rubber, PVC, polyurethane, EVA, TPR, etc. Among them, the anti-skid performance of PVC material soles is not as good as that of rubber, but its waterproof and acid-base resistance is better; TPR material soles have higher elasticity, but are not suitable for outdoor anti-skid. In applications in humid ground environments, the friction between the sole and the ground is weakened, resulting in a decrease in the anti-skid performance of the sole. Therefore, we propose a flame-retardant anti-skid sole and its manufacturing process. Summary of the invention
[0003] The object of the present invention is to provide a flame retardant anti-skid sole and a manufacturing process thereof, so as to solve the problems raised in the above background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solution: a flame retardant and anti-slip sole, comprising the following components by mass: 100 parts of rubber material, 15 to 25 parts of filler, 10 to 15 parts of plasticizer, 2.5 to 3.2 parts of foaming agent, 1.2 to 5.0 parts of zinc oxide, 7 to 11 parts of calcium carbonate, and 4.5 to 8.0 parts of auxiliary materials.
[0005] Furthermore, the rubber material includes 50 to 60 parts of chlorinated polyethylene, 25 to 30 parts of ethylene-vinyl acetate copolymer, and 10 to 25 parts of silicone rubber.
[0006] In the above technical scheme, the rubber material includes chlorinated polyethylene (CM), ethylene-vinyl acetate copolymer (EVA) and silicone rubber. Chlorinated polyethylene is a polymer obtained by substitution of polyethylene with chlorine. When its chlorine content reaches 30% to 45%, it behaves as a rubber elastomer with good elasticity and mechanical properties. In the use of ethylene-vinyl acetate copolymer in shoe materials, the vinyl acetate content is generally 15% to 22%, and it has the properties of softness, good elasticity, and chemical corrosion resistance. The rubber material is also added with silicone rubber with good wear resistance and tear resistance, oil resistance, acid and alkali resistance, anti-skid and cushioning properties. Chlorinated polyethylene, ethylene-vinyl acetate copolymer, and silicone rubber are compositely foamed to form uniform bubbles in the sole material. Compared with the unfoamed sole material, the sole material has a lower density and better softness, shock absorption, and anti-skid properties.
[0007] Furthermore, the filler is one of porous silicon powder, white carbon black, fumed silica, activated carbon, tetrapod-shaped zinc oxide whiskers, and silicon carbide crystals.
[0008] Furthermore, the foaming agent is a mixture of azodicarbonamide and diisopropylbenzene peroxide in a mass ratio of (1.5-2.0):1.
[0009] Furthermore, the auxiliary materials include 1.0 to 1.6 parts of lubricant, 0.5 to 1.5 parts of antioxidant, 0.2 to 0.5 parts of anti-scorch agent, 1.6 to 2.0 parts of vulcanizing agent, and 1.2 to 2.4 parts of accelerator.
[0010] Further, the plasticizer is one of dibutyl phthalate and dioctyl phthalate;
[0011] The lubricant is one of stearic acid, zinc stearate, and calcium stearate;
[0012] The antioxidant is a mixture of antioxidant RD and antioxidant CPPD, with a mass ratio of 2:1;
[0013] The anti-scorch agent is anti-scorch agent CTP;
[0014] The vulcanizing agent is one of sulfur and vulcanizing agent DTDM;
[0015] The accelerator is a mixture of accelerator DM and accelerator TETD, with a mass ratio of 5:1.
[0016] Furthermore, the silicone rubber is prepared by the following process:
[0017] Mix ferrocene carboxylic acid, unsaturated monomer, 4-dimethylaminopyridine and anhydrous dichloromethane, cool to 0-3°C in a nitrogen atmosphere, and stir for 30-45 minutes; slowly add N,N'-dicyclohexylcarbodiimide within 60 minutes, and then continue to stir for 60-75 minutes; restore the system temperature to room temperature and stir for 24 hours; filter, concentrate the filtrate, elute, chromatograph, and rotary evaporate to obtain ferrocene monomer;
[0018] Mix bromoisobutyl silicone rubber, ferrocene monomer, N,N,N,N,N-pentamethyldiethyltriamine and anisole, add cuprous bromide under nitrogen atmosphere, raise the temperature to 90-95°C, and react for 7-8h. After the reaction, introduce air, add tetrahydrofuran, pass through a column, rotary evaporate, dissolve with tetrahydrofuran and ether, precipitate and dry in vacuum to obtain silicone rubber.
[0019] Further, the mass ratio of ferrocene carboxylic acid, unsaturated monomer, 4-dimethylaminopyridine, and N,N'-dicyclohexylcarbodiimide (DCC) is (4.5-4.8):10:(0.14-0.15):(2.3-2.4);
[0020] The ratio of ferrocene carboxylic acid to anhydrous dichloromethane is 2 g / 100 mL.
[0021] Furthermore, the mass ratio of bromoisobutyl silicone rubber, ferrocene monomer, N,N,N,N,N-pentamethyldiethyltriamine, anisole and cuprous bromide is 100:(20-30):(0.40-0.46):(1.0-1.2):(0.40-0.46).
[0022] Further, the unsaturated monomer is prepared by the following process:
[0023] Mix 2,2'-p-phenyl-bis(5-aminobenzoxazole) and a catalyst in dichloromethane, add phosphorus oxychloride under nitrogen atmosphere, stir for 5-8 minutes, add triethylamine, heat to 40-50°C, and react for 6-7 hours; remove the solvent and unreacted phosphorus oxychloride by vacuum distillation, filter, and dry to obtain benzothiazole-phosphoryl dichloride;
[0024] Mix benzothiazole-phosphoryl dichloride and butenediol in dichloromethane, heat to 40-50°C under nitrogen atmosphere, and reflux for 100-150 minutes; distill under reduced pressure, filter, dry, and recrystallize using chloroform to obtain an unsaturated monomer.
[0025] Further, the molar ratio of 2,2'-p-phenyl-bis(5-aminobenzoxazole) (CAS No.: 13752-53-9) and phosphorus oxychloride is 1:(2.5-3.0);
[0026] The ratio of 2,2'-p-phenyl-bis(5-aminobenzoxazole) and dichloromethane is 5 g / 100 mL;
[0027] The mass of the catalyst tetrabutylammonium bromide is 4-5% of the mass of 2,2'-p-phenyl-bis(5-aminobenzoxazole).
[0028] Further, the mass ratio of benzothiazole-phosphoryl dichloride to butene glycol is 10:(6-8);
[0029] The ratio of benzothiazole-phosphoryl dichloride to dichloromethane is 5 g / 100 mL.
[0030] Furthermore, the bromine-containing isobutyl silicone rubber is prepared by the following process:
[0031] The aminopolydimethylsiloxane and tetrahydrofuran are mixed, and diisocyanate is slowly added under nitrogen atmosphere protection and temperature of 0-2°C, and the addition is completed within 30 minutes, and the reaction is carried out for 8-9 hours; 2,2'-p-phenyl-bis(5-aminobenzoxazole) is slowly added within 30 minutes, and the reaction is carried out for 90-120 minutes; 1,4-butanediol is added, and the temperature is raised to 80-88°C, and the reaction is continued for 4-5 hours; the solvent is removed by rotary evaporation, and deionized water and methanol are used for flocculation and washing, and vacuum drying is carried out to constant weight to obtain hydroxy silicone rubber;
[0032] Mix 2-bromoisobutyric acid and thionyl chloride in toluene, reflux for 30-60 minutes to obtain acid chloride, remove toluene and excess thionyl chloride by vacuum distillation, slowly add to the tetrahydrofuran solution of hydroxy silicone rubber within 30 minutes, react for 8-12 hours, rotary evaporate, wash, and vacuum dry to constant weight to obtain bromine-containing isobutyl silicone rubber.
[0033] In the above technical scheme, the unsaturated monomer is obtained by reacting 2,2'-p-phenyl-bis(5-aminobenzothiazole), phosphorus oxychloride and butenediol, and the chlorine group in phosphorus oxychloride reacts with the amino group in 2,2'-p-phenyl-bis(5-aminobenzothiazole) and the hydroxyl group in butenediol in sequence; and by setting the amount of reactants added, a polyhydroxy unsaturated monomer having a phenyl, bisbenzothiazole structure and nitrogen and phosphorus elements is formed.
[0034] The bromine-containing isobutyl silicone rubber is prepared from amino polydimethylsiloxane, diisocyanate, 2,2'-p-phenyl-bis(5-aminobenzoxazole), 1,4-butanediol and 2-bromoisobutyric acid. The polyhydroxy silicone rubber (denoted as hydroxy silicone rubber) is obtained by the reaction and chain extension of diisocyanate with the amino groups in amino polydimethylsiloxane and 2,2'-p-phenyl-bis(5-aminobenzoxazole) and the hydroxy groups in 1,4-butanediol. The hydroxy groups are reacted and esterified with the carboxyl groups in 2-bromoisobutyric acid to obtain bromine-containing isobutyl silicone rubber. While achieving a high molecular weight of the silicone rubber, phenyl, benzothiazole structure and nitrogen element are introduced to prepare bromine-containing isobutyl silicone rubber with an initiating effect.
[0035] By polymerizing unsaturated monomers in a system containing bromine isobutyl silicone rubber, phenyl, dibenzothiazole structures and nitrogen and phosphorus elements are introduced together, their content in the sole material is increased, and steric hindrance is generated, so that the free volume in the sole material is increased, which helps to improve the strength and toughness and impact resistance of the sole material; it also helps to improve the strength and stability of the carbon layer during the combustion of the sole material, forming a flame-retardant carbon layer protection, effectively blocking the exchange of substances and heat, promoting the synergistic flame retardancy of the gas phase and the condensed phase and the improvement of the flame retardancy of the two, and improving the thermal stability and flame retardancy of the sole material.
[0036] In the above technical scheme, the unsaturated monomer contains hydroxyl and double bond, and its hydroxyl reacts with ferrocene carboxylic acid to esterify, generating ferrocene functionalized ferrocene monomer; and the silicone rubber (containing bromoisobutyl silicone rubber) as the reactant contains bromoisobutyl, under its initiation, the polymerization of ferrocene monomer can be realized, so that the prepared ferrocene polymer is assembled with the silicone rubber molecular structure to form a three-dimensional network, and the entanglement of the system is promoted, which is helpful to improve the strength of the sole material. Ferrocene is introduced into the silicone rubber and sole material system, as an organic transition metal compound with high stability and chemical stability, it can cooperate with the molecular structure system of silicone rubber and unsaturated monomers, participate in the carbonization of the condensed phase, help the densification of the carbon layer, prevent the transfer of heat and substances, and improve the flame retardant and smoke suppression capabilities of the prepared sole material.
[0037] Further, the bromine-isobutyl silicone rubber is prepared from the following components by mass: 10 parts of amino polydimethylsiloxane, 1 to 5 parts of diisocyanate, 1.2 to 2.0 parts of 2,2'-p-phenyl-bis(5-aminobenzoxazole), 0.3 to 1.5 parts of 1,4-butanediol, and 0.56 to 2.78 parts of 2-bromoisobutyric acid;
[0038] The ratio of aminopolydimethylsiloxane and tetrahydrofuran is 5g:100mL;
[0039] Diisocyanate and 2,2'-p-phenyl-bis(5-aminobenzoxazole) were added in the form of tetrahydrofuran solution, with a mass concentration of 5%;
[0040] The diisocyanate is one of isophorone diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,6-diisocyanatohexane, 4,4'-diisocyanate dicyclohexylmethane, and p-phenylene diisocyanate;
[0041] Aminopolydimethylsiloxane: α,ω-bis(3-aminopropyl)polydimethylsiloxane (PDMS), Mn=1000-5000, sourced from Gorest Group Co., Ltd., Germany.
[0042] Furthermore, the filler is modified, and the specific modification process is:
[0043] Under the protection of nitrogen atmosphere, ferrocenylimidate methyl ester and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane are mixed in anhydrous ethanol and stirred for 60 to 75 minutes; the temperature is raised to 80 to 100° C. and refluxed for 6 to 8 hours; and the coupling agent is obtained by rotary evaporation;
[0044] The coupling agent, filler and ethanol solution are mixed, heated to 58-62° C., and reacted for 160-200 minutes; the mixture is washed with deionized water, saturated sodium carbonate solution and saturated sodium chloride solution, and dried to obtain a modified filler.
[0045] Further, the molar ratio of ferrocenylimidate and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane is 1:1;
[0046] The ratio of methyl ferrocenylimidate to anhydrous ethanol is 1 g / 100 mL.
[0047] Furthermore, the ratio of coupling agent, filler and ethanol solution is (0.3-1.0) g:10 g:100 mL; and the concentration of ethanol solution is 85 wt %.
[0048] A manufacturing process for a flame retardant anti-skid sole, comprising the following processes:
[0049] The rubber material, filler, plasticizer, foaming agent, zinc oxide, calcium carbonate and auxiliary materials are added to an open mill for plasticizing to obtain a mixed material; the mixed material is extruded and granulated through a single screw extruder to obtain a composite material;
[0050] The material is heated into a flat mold through an injection molding machine, vulcanized and foamed to obtain the sole material; the surface is oxidized to obtain a flame retardant and non-slip sole.
[0051] Furthermore, the process conditions of the plasticating are: temperature 100-110° C., time 12-20 min.
[0052] Furthermore, the extrusion process conditions are: extrusion temperature 180-200° C., screw speed 30-40 r / min.
[0053] Furthermore, the process conditions of vulcanization and foaming are: temperature 172-178° C., time 10-12 min.
[0054] Furthermore, the process conditions of the surface oxidation are: contacting the surface of the sole material with the oxide solution for 12 to 24 hours; then washing and drying;
[0055] The oxides are peroxide and potassium permanganate.
[0056] Furthermore, the oxide solution is a 30 wt % hydrogen peroxide solution.
[0057] In the above technical solution, after the sole material is prepared, the surface of the sole material is subjected to oxidation treatment, and the rubber material and ferrocene structure in the surface system are oxidized to form hydrophilic ferrocene cations and oxidation products, which cooperate with the thiazole structure to make the sole surface have a certain hydrophilicity in the rain environment. The wetting of water molecules on the sole surface can promote the increase of friction between the sole material and the ground, which helps to improve the anti-skid ability of the sole material. Fillers such as porous silica powder and white carbon black are porous, and the improvement of hydrophilicity helps to retain water in the porous surface of the sole, further improving the anti-skid ability of the sole material, thereby realizing the preparation of flame-retardant anti-skid soles.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] 1. The flame retardant and anti-skid sole described in the present invention adopts chlorinated polyethylene (CM), ethylene-vinyl acetate copolymer (EVA) and silicone rubber as rubber materials, which are compositely foamed to form uniform pores to prepare a sole material with low density and excellent softness, shock absorption and anti-skid performance.
[0060] 2. The flame-retardant and anti-skid sole described in the present invention is prepared by reacting 2,2'-p-phenyl-bis(5-aminobenzoxazole), phosphorus oxychloride and butene glycol to prepare an unsaturated monomer, which is then reacted with ferrocene carboxylic acid for esterification to generate a ferrocene-functionalized ferrocene monomer; aminopolydimethylsiloxane, diisocyanate, 2,2'-p-phenyl-bis(5-aminobenzoxazole), 1,4-butanediol and 2-bromoisobutyric acid to prepare bromoisobutyl silicone rubber, which exerts its initiating effect to polymerize the ferrocene monomer to obtain silicone rubber, which can effectively improve the strength and flame retardancy of the sole material.
[0061] 3. The flame retardant and anti-skid sole described in the present invention has a certain hydrophilicity on the surface of the sole material by oxidation treatment, which promotes the increase of friction between the sole material and the ground and improves the anti-skid ability of the sole material. The porous silica powder, white carbon black and other fillers are porous, which helps to retain water in the porous surface of the sole, further improving the anti-skid ability of the sole material, thereby realizing the preparation of the flame retardant and anti-skid sole. DETAILED DESCRIPTION
[0062] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0063] In the following specific implementations,
[0064] Chlorinated polyethylene (CM): 135B, 36% chlorine content, sourced from Weifang Yaxing Chemical Co., Ltd.
[0065] Ethylene-vinyl acetate copolymer (EVA): 18J3, vinyl acetate content 18%, sourced from Sinopec Yanshan Petrochemical Company.
[0066] The filler is fumed silica SR-2200, which comes from Anhui Evolution Silica Nanomaterials Technology Co., Ltd.
[0067] The foaming agent is a mixture of azodicarbonamide and dicumyl peroxide, with a mass ratio of 1.8:1;
[0068] The plasticizer is dibutyl phthalate; the lubricant is stearic acid; the antioxidant is a mixture of antioxidant RD and antioxidant CPPD, with a mass ratio of 2:1; the anti-scorch agent is anti-scorch agent CTP; the vulcanizing agent is vulcanizing agent DTDM; the accelerator is a mixture of accelerator DM and accelerator TETD, with a mass ratio of 5:1;
[0069] Aminopolydimethylsiloxane: α,ω-bis(3-aminopropyl)polydimethylsiloxane (PDMS), Mn=3000, from Gorest Group Co., Ltd., Germany;
[0070] Ferrocene methyl imidate was prepared by the following process: 60 mL of anhydrous ether and 18 mL of anhydrous methanol were mixed, 3.0 g of cyanoferrocene was added, hydrogen chloride gas was introduced at 0°C until the solution was saturated, the solution was returned to room temperature, and the reaction was carried out for 10 hours; rotary evaporation and washing were performed;
[0071] The "parts" mentioned are all parts by mass.
[0072] Embodiment 1: A process for manufacturing a flame retardant anti-skid sole, comprising the following processes:
[0073] Step (1) Preparation of silicone rubber:
[0074] 1.1. Mix 5g of 2,2'-p-phenyl-bis(5-aminobenzoxazole) and 0.20g of catalyst tetrabutylammonium bromide in 100mL of dichloromethane, add 5.6g of phosphorus oxychloride under nitrogen atmosphere, stir for 5min, add 1.8g of triethylamine, heat to 40°C, and react for 7h; remove the solvent and unreacted phosphorus oxychloride by vacuum distillation, filter and dry to obtain benzothiazole-phosphoryl dichloride;
[0075] 5 g of benzothiazole-phosphoryl dichloride and 3 g of butenediol were mixed in 100 mL of dichloromethane, heated to 40°C under nitrogen atmosphere, and refluxed for 150 min; vacuum distilled, filtered, dried, and recrystallized from chloroform to obtain an unsaturated monomer;
[0076] 1.2. Brominated isobutyl silicone rubber is prepared by the following process:
[0077] 5 g of amino polydimethylsiloxane and 100 mL of tetrahydrofuran were mixed, and under nitrogen atmosphere protection and temperature of 2°C, 5% tetrahydrofuran solution of isophorone diisocyanate was slowly added within 30 minutes, and the reaction was carried out for 8 hours; 5% tetrahydrofuran solution of 2,2'-p-phenyl-bis(5-aminobenzoxazole) was slowly added within 30 minutes, and the reaction was carried out for 90 minutes; 1,4-butanediol was added, the temperature was raised to 80°C, and the reaction was continued for 5 hours; the solvent was removed by rotary evaporation, and deionized water and methanol were used for flocculation and washing, and vacuum drying was carried out to constant weight to obtain hydroxy silicone rubber;
[0078] 2-bromoisobutyric acid and thionyl chloride are mixed in toluene, and refluxed for 30 minutes to obtain acid chloride, and toluene and excess thionyl chloride are removed by vacuum distillation, and then slowly added to a tetrahydrofuran solution of hydroxy silicone rubber within 30 minutes, and the reaction is carried out for 8 hours; rotary evaporation, washing, and vacuum drying to constant weight are performed to obtain bromoisobutyl silicone rubber; bromoisobutyl silicone rubber is prepared from the following mass components: 10 parts of aminopolydimethylsiloxane, 1 part of isophorone diisocyanate, 1.2 parts of 2,2'-p-phenyl-bis(5-aminobenzoxazole), 0.3 parts of 1,4-butanediol, and 0.56 parts of 2-bromoisobutyric acid;
[0079] 1.3. Mix 2g of ferrocene carboxylic acid, unsaturated monomer, and 4-dimethylaminopyridine with 100mL of anhydrous dichloromethane, cool to 3°C in a nitrogen atmosphere, and stir for 30min; slowly add N,N'-dicyclohexylcarbodiimide within 60min, and then continue stirring for 60min; restore the system temperature to room temperature and stir for 24h; filter, concentrate the filtrate, elute, chromatograph, and rotary evaporate to obtain ferrocene monomer; the mass ratio of ferrocene carboxylic acid, unsaturated monomer, 4-dimethylaminopyridine, and N,N'-dicyclohexylcarbodiimide is 4.5:10:0.14:2.3;
[0080] Mix bromoisobutyl silicone rubber, ferrocene monomer, N,N,N,N,N-pentamethyldiethyltriamine and anisole, add cuprous bromide under nitrogen atmosphere, heat to 90°C and react for 8h; after the reaction, introduce air, add tetrahydrofuran, pass through a column, rotary evaporate, dissolve with tetrahydrofuran and ether, precipitate and dry in vacuum to obtain silicone rubber; the mass ratio of bromoisobutyl silicone rubber, ferrocene monomer, N,N,N,N,N-pentamethyldiethyltriamine, anisole and cuprous bromide is 100:20:0.40:1.0:0.40;
[0081] Step (2) Modification of filler:
[0082] Under nitrogen atmosphere, 1 g of ferrocenylimidate and 0.8 g of N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane were mixed in 100 mL of anhydrous ethanol and stirred for 60 min; the temperature was raised to 80° C. and refluxed for 8 h; and the coupling agent was obtained by rotary evaporation;
[0083] 0.3 g of coupling agent, 10 g of filler, and 100 mL of 85 wt% ethanol solution were mixed, heated to 58° C., and reacted for 200 min; the mixture was washed with deionized water, saturated sodium carbonate solution, and saturated sodium chloride solution, and dried to obtain a modified filler;
[0084] Step (3) Preparation of flame retardant anti-skid sole:
[0085] 60 parts of chlorinated polyethylene, 30 parts of ethylene-vinyl acetate copolymer, 10 parts of silicone rubber, 15 parts of filler, 10 parts of plasticizer, 2.5 parts of foaming agent, 1.2 parts of zinc oxide, 7 parts of calcium carbonate, 1.0 parts of lubricant, 0.5 parts of antioxidant, 0.2 parts of anti-scorch agent, 1.6 parts of vulcanizing agent, and 1.2 parts of accelerator are added to an open mill for plasticizing. The plasticizing process conditions are: temperature 100°C, time length 20min, to obtain a mixed material; extruded through a single screw extruder, the extrusion process conditions are: extrusion temperature 180°C, screw speed 30r / min, granulated, to obtain a composite material;
[0086] The material is heated into a flat mold by an injection molding machine, vulcanized and foamed, and the process conditions are: temperature 172°C, time 12 minutes, to obtain a sole material; the surface of the sole material is contacted with a 30wt% hydrogen peroxide solution for 12 hours for surface oxidation, and then washed and dried to obtain a flame-retardant and anti-slip sole.
[0087] Embodiment 2: A process for producing a flame retardant anti-skid sole, comprising the following processes:
[0088] Step (1) Preparation of silicone rubber:
[0089] 1.1. Mix 5g of 2,2'-p-phenyl-bis(5-aminobenzoxazole) and 0.23g of catalyst tetrabutylammonium bromide in 100mL of dichloromethane, add 6.2g of phosphorus oxychloride under nitrogen atmosphere, stir for 6min, add 1.8g of triethylamine, heat to 45°C, and react for 6.5h; remove the solvent and unreacted phosphorus oxychloride by vacuum distillation, filter and dry to obtain benzothiazole-phosphoryl dichloride;
[0090] 5 g of benzothiazole-phosphoryl dichloride and 3.5 g of butenediol were mixed in 100 mL of dichloromethane, heated to 45°C under nitrogen atmosphere, and refluxed for 120 min; distilled under reduced pressure, filtered, dried, and recrystallized from chloroform to obtain an unsaturated monomer;
[0091] 1.2. Brominated isobutyl silicone rubber is prepared by the following process:
[0092] 5 g of amino polydimethylsiloxane and 100 mL of tetrahydrofuran were mixed, and a 5% tetrahydrofuran solution of isophorone diisocyanate was slowly added under nitrogen atmosphere protection and at a temperature of 1°C. The addition was completed within 30 minutes and the reaction was carried out for 8.5 hours. A 5% tetrahydrofuran solution of 2,2'-p-phenyl-bis(5-aminobenzoxazole) was slowly added within 30 minutes and the reaction was carried out for 105 minutes. 1,4-butanediol was added, the temperature was raised to 85°C, and the reaction was continued for 4.5 hours. The solvent was removed by rotary evaporation, and deionized water and methanol were used for flocculation and washing, and vacuum drying was carried out to constant weight to obtain hydroxy silicone rubber.
[0093] 2-bromoisobutyric acid and thionyl chloride are mixed in toluene, and refluxed for 45 minutes to obtain acid chloride, and toluene and excess thionyl chloride are removed by vacuum distillation, and then slowly added to a tetrahydrofuran solution of hydroxy silicone rubber within 30 minutes, and the reaction is carried out for 10 hours; rotary evaporation, washing, and vacuum drying to constant weight are performed to obtain bromoisobutyl silicone rubber; bromoisobutyl silicone rubber is prepared from the following mass components: 10 parts of aminopolydimethylsiloxane, 3 parts of isophorone diisocyanate, 1.6 parts of 2,2'-p-phenyl-bis(5-aminobenzoxazole), 0.9 parts of 1,4-butanediol, and 1.67 parts of 2-bromoisobutyric acid;
[0094] 1.3. Mix 2g of ferrocene carboxylic acid, unsaturated monomer, and 4-dimethylaminopyridine with 100mL of anhydrous dichloromethane, cool to 1°C in a nitrogen atmosphere, and stir for 38min; slowly add N,N'-dicyclohexylcarbodiimide within 60min, and then continue stirring for 68min; restore the system temperature to room temperature and stir for 24h; filter, concentrate the filtrate, elute, chromatograph, and rotary evaporate to obtain ferrocene monomer; the mass ratio of ferrocene carboxylic acid, unsaturated monomer, 4-dimethylaminopyridine, and N,N'-dicyclohexylcarbodiimide is 4.6:10:0.14:2.4;
[0095] Mix bromoisobutyl silicone rubber, ferrocene monomer, N,N,N,N,N-pentamethyldiethyltriamine and anisole, add cuprous bromide under nitrogen atmosphere, heat to 92°C and react for 7.5h; after the reaction, introduce air, add tetrahydrofuran, pass through a column, rotary evaporate, dissolve with tetrahydrofuran and ether, precipitate and dry in vacuum to obtain silicone rubber; the mass ratio of bromoisobutyl silicone rubber, ferrocene monomer, N,N,N,N,N-pentamethyldiethyltriamine, anisole and cuprous bromide is 100:25:0.43:1.1:0.43;
[0096] Step (2) Modification of filler:
[0097] Under nitrogen atmosphere, 1 g of ferrocenylimidate and 0.8 g of N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane were mixed in 100 mL of anhydrous ethanol and stirred for 68 min; the temperature was raised to 90° C. and refluxed for 7 h; and the coupling agent was obtained by rotary evaporation;
[0098] 0.6 g of coupling agent, 10 g of filler, and 100 mL of 85 wt% ethanol solution were mixed, heated to 60° C., and reacted for 180 min; the mixture was washed with deionized water, saturated sodium carbonate solution, and saturated sodium chloride solution, and dried to obtain a modified filler;
[0099] Step (3) Preparation of flame retardant anti-skid sole:
[0100] 55 parts of chlorinated polyethylene, 27 parts of ethylene-vinyl acetate copolymer, 18 parts of silicone rubber, 20 parts of filler, 12 parts of plasticizer, 2.8 parts of foaming agent, 3.1 parts of zinc oxide, 9 parts of calcium carbonate, 1.3 parts of lubricant, 1.0 parts of antioxidant, 0.3 parts of anti-scorch agent, 1.8 parts of vulcanizer, and 1.8 parts of accelerator are added to an open mill for plasticizing. The plasticizing process conditions are: temperature 105°C, time length 16 minutes, to obtain a mixed material; extruded through a single screw extruder, the extrusion process conditions are: extrusion temperature 190°C, screw speed 35r / min, granulated, to obtain a composite material;
[0101] The material is heated into a flat mold through an injection molding machine, vulcanized and foamed, and the process conditions are: temperature 175°C, time 11 minutes, to obtain a sole material; the surface of the sole material is contacted with a 30wt% hydrogen peroxide solution for 18 hours for surface oxidation, and then washed and dried to obtain a flame-retardant and anti-slip sole.
[0102] Embodiment 3: A process for manufacturing a flame retardant anti-skid sole, comprising the following processes:
[0103] Step (1) Preparation of silicone rubber:
[0104] 1.1. Mix 5g of 2,2'-p-phenyl-bis(5-aminobenzoxazole) and 0.25g of catalyst tetrabutylammonium bromide in 100mL of dichloromethane, add 6.7g of phosphorus oxychloride under nitrogen atmosphere, stir for 8min, add 1.8g of triethylamine, heat to 50°C, and react for 6h; remove the solvent and unreacted phosphorus oxychloride by vacuum distillation, filter and dry to obtain benzothiazole-phosphoryl dichloride;
[0105] 5 g of benzothiazole-phosphoryl dichloride and 4 g of butenediol were mixed in 100 mL of dichloromethane, heated to 50°C under nitrogen atmosphere, and refluxed for 100 min; distilled under reduced pressure, filtered, dried, and recrystallized from chloroform to obtain an unsaturated monomer;
[0106] 1.2. Brominated isobutyl silicone rubber is prepared by the following process:
[0107] 5 g of amino polydimethylsiloxane and 100 mL of tetrahydrofuran were mixed, and under nitrogen atmosphere protection and temperature of 0°C, 5% tetrahydrofuran solution of isophorone diisocyanate was slowly added within 30 minutes, and the reaction was carried out for 9 hours; 5% tetrahydrofuran solution of 2,2'-p-phenyl-bis(5-aminobenzoxazole) was slowly added within 30 minutes, and the reaction was carried out for 120 minutes; 1,4-butanediol was added, the temperature was raised to 88°C, and the reaction was continued for 4 hours; the solvent was removed by rotary evaporation, and deionized water and methanol were used for flocculation and washing, and vacuum drying was carried out to constant weight to obtain hydroxy silicone rubber;
[0108] 2-bromoisobutyric acid and thionyl chloride are mixed in toluene, and refluxed for 60 minutes to obtain acid chloride, and toluene and excess thionyl chloride are removed by vacuum distillation, and then slowly added to a tetrahydrofuran solution of hydroxy silicone rubber within 30 minutes, and the reaction is carried out for 12 hours; rotary evaporation, washing, and vacuum drying to constant weight are performed to obtain bromoisobutyl silicone rubber; bromoisobutyl silicone rubber is prepared from the following mass components: 10 parts of aminopolydimethylsiloxane, 5 parts of isophorone diisocyanate, 2.0 parts of 2,2'-p-phenyl-bis(5-aminobenzoxazole), 1.5 parts of 1,4-butanediol, and 2.78 parts of 2-bromoisobutyric acid;
[0109] 1.3. Mix 2g of ferrocene carboxylic acid, unsaturated monomer, and 4-dimethylaminopyridine with 100mL of anhydrous dichloromethane, cool to 0°C in a nitrogen atmosphere, and stir for 45min; slowly add N,N'-dicyclohexylcarbodiimide within 60min, and then continue stirring for 75min; restore the system temperature to room temperature and stir for 24h; filter, concentrate the filtrate, elute, chromatograph, and rotary evaporate to obtain ferrocene monomer; the mass ratio of ferrocene carboxylic acid, unsaturated monomer, 4-dimethylaminopyridine, and N,N'-dicyclohexylcarbodiimide is 4.8:10:0.15:2.4;
[0110] Mix bromoisobutyl silicone rubber, ferrocene monomer, N,N,N,N,N-pentamethyldiethyltriamine and anisole, add cuprous bromide under nitrogen atmosphere, heat to 95°C and react for 7h; after the reaction, introduce air, add tetrahydrofuran, pass through a column, rotary evaporate, dissolve with tetrahydrofuran and ether, precipitate and dry in vacuum to obtain silicone rubber; the mass ratio of bromoisobutyl silicone rubber, ferrocene monomer, N,N,N,N,N-pentamethyldiethyltriamine, anisole and cuprous bromide is 100:30:0.46:1.2:0.46;
[0111] Step (2) Modification of filler:
[0112] Under nitrogen atmosphere, 1 g of ferrocenylimidate and 0.8 g of N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane were mixed in 100 mL of anhydrous ethanol and stirred for 75 min; the temperature was raised to 100 ° C and refluxed for 6 h; rotary evaporation was performed to obtain a coupling agent;
[0113] 1.0 g of coupling agent, 10 g of filler, and 100 mL of 85 wt% ethanol solution were mixed, heated to 62° C., and reacted for 160 min; the mixture was washed with deionized water, saturated sodium carbonate solution, and saturated sodium chloride solution, and dried to obtain a modified filler;
[0114] Step (3) Preparation of flame retardant anti-skid sole:
[0115] 50 parts of chlorinated polyethylene, 25 parts of ethylene-vinyl acetate copolymer, 25 parts of silicone rubber, 25 parts of filler, 15 parts of plasticizer, 3.2 parts of foaming agent, 5.0 parts of zinc oxide, 11 parts of calcium carbonate, 1.6 parts of lubricant, 1.5 parts of antioxidant, 0.5 parts of anti-scorch agent, 2.0 parts of vulcanizing agent, and 2.4 parts of accelerator are added to an open mill for plasticizing. The plasticizing process conditions are: temperature 110° C., time length 12 min, to obtain a mixed material; extruded through a single screw extruder, the extrusion process conditions are: extrusion temperature 200° C., screw speed 30 r / min, granulated, to obtain a composite material;
[0116] The material is heated into a flat mold through an injection molding machine, vulcanized and foamed, and the process conditions are: temperature 178°C, time 10 minutes, to obtain a sole material; the surface of the sole material is contacted with a 30wt% hydrogen peroxide solution for 24 hours for surface oxidation, and then washed and dried to obtain a flame-retardant and anti-slip sole.
[0117] Comparative Example 1: A process for producing a flame-retardant anti-skid sole, comprising the following processes:
[0118] Steps (1-2) are the same as those in Comparative Example 1, and surface oxidation is not performed in step (3). The prepared sole material is used as the flame-retardant and anti-slip sole in Comparative Example 1.
[0119] Comparative Example 2: A process for producing a flame-retardant anti-skid sole, comprising the following processes:
[0120] 0.3g coupling agent KH-550, 10g filler, 100mL 85wt% ethanol solution were mixed, heated to 58°C, and reacted for 200min; the mixture was washed with deionized water, saturated sodium carbonate solution, and saturated sodium chloride solution, and dried to obtain a modified filler.
[0121] Step (2) is the same as that in Comparative Example 1, and surface oxidation is not performed in step (3). The prepared sole material is used as the flame-retardant and anti-slip sole in Comparative Example 1.
[0122] Comparative Example 3: A process for producing a flame-retardant anti-skid sole, comprising the following processes:
[0123] Step (1) Preparation of silicone rubber:
[0124] 2 g of ferrocene carboxylic acid, hydroxyethyl methacrylate and 4-dimethylaminopyridine were mixed with 100 mL of anhydrous dichloromethane, cooled to 3°C in a nitrogen atmosphere, and stirred for 30 min; N,N'-dicyclohexylcarbodiimide was slowly added within 60 min, and then stirred for 60 min; the system temperature was restored to room temperature and stirred for 24 h; filtered, the filtrate was concentrated, eluted, chromatographed, and rotary evaporated to obtain ferrocene monomer; the mass ratio of ferrocene carboxylic acid, unsaturated monomer, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbodiimide was 4.5:1.5:0.14:2.3;
[0125] Mix bromoisobutyl silicone rubber, ferrocene monomer, N,N,N,N,N-pentamethyldiethyltriamine and anisole, add cuprous bromide under nitrogen atmosphere, heat to 90°C and react for 8h; after the reaction, introduce air, add tetrahydrofuran, pass through a column, rotary evaporate, dissolve with tetrahydrofuran and ether, precipitate and dry in vacuum to obtain silicone rubber; the mass ratio of bromoisobutyl silicone rubber, ferrocene monomer, N,N,N,N,N-pentamethyldiethyltriamine, anisole and cuprous bromide is 100:20:0.40:1.0:0.40;
[0126] The preparation of the bromine-isobutyl silicone rubber and steps (2-3) are the same as those in Comparative Example 1 to obtain a flame-retardant and anti-skid sole.
[0127] Comparative Example 4: A process for producing a flame-retardant anti-skid sole, comprising the following processes:
[0128] Step (1) Preparation of silicone rubber:
[0129] 5 g of aminopolydimethylsiloxane and 100 mL of tetrahydrofuran were mixed, and a 5% tetrahydrofuran solution of isophorone diisocyanate was slowly added within 30 min under nitrogen atmosphere and at 2°C, and the reaction was continued for 8 h; 1,4-butanediol was slowly added within 30 min, and the temperature was raised to 80°C, and the reaction was continued for 5 h; the solvent was removed by rotary evaporation, and deionized water and methanol were used for flocculation and washing, and vacuum drying was performed to constant weight to obtain silicone rubber;
[0130] Steps (2-3) are the same as those in Comparative Example 1 to obtain a flame retardant and anti-skid sole.
[0131] Experiment: Take the flame retardant and anti-skid soles obtained in Examples 1-3 and Comparative Examples 1-4, prepare samples, test their properties respectively and record the test results:
[0132] Anti-slip performance test: The sample was conditioned in an environment of 25°C and 50RH% for 16 hours. The static anti-slip performance of the sample was tested with reference to HG / T 3780. The fixture was pulled horizontally at a speed of 100mm / min. The sample size was Φ12.5mm×7mm. The experimental conditions were 25°C and 50RH%. The ratio of the average value of the maximum pulling force in the four directions of the sample to the positive pressure of the sample was taken as the static friction coefficient of the sample (dry method).
[0133] The wet method medium is water. Place the sample on the friction panel and let it stand for 30 seconds. Repeat the above operation to obtain the static friction coefficient of the sample (wet method).
[0134] Flame retardant performance test: Using ASTM D 3801 as the reference standard, a vertical combustion test was conducted on the sample using a vertical and horizontal combustion test machine. The sample size was 125mm×13mm×2mm.
[0135] Taking GB / T 10707 as the reference standard, the oxygen index tester was used to test the limiting oxygen index (LOI) of the sample, and the sample size was 130mm×6.5mm×2mm;
[0136] Mechanical properties test: GB / T 528 was used as the reference standard, and the tensile properties of the samples were tested using an electronic tensile machine at a tensile rate of 500 mm / min.
[0137] Taking GB / T 529 as reference standard, the tearing properties of the samples were tested.
[0138]
[0139]
[0140] According to the data in the above table, we can clearly draw the following conclusions:
[0141] The flame retardant and anti-skid soles obtained in Examples 1-3 are compared with the flame retardant and anti-skid soles obtained in Comparative Examples 1-4. The test results show that:
[0142] Compared with the comparative example, the flame retardant and anti-skid soles obtained in Examples 1-3 have higher dry and wet friction coefficients, limiting oxygen index, tensile strength and tear strength data, which fully demonstrates that the present invention achieves the improvement of the flame retardant ability, anti-skid performance and mechanical properties of the flame retardant and anti-skid soles.
[0143] Compared with Example 1, surface oxidation was not performed in step (3) of Comparative Example 1, and the prepared sole material was used as the flame-retardant and anti-slip sole in Comparative Example 1; its dry and wet friction coefficients decreased significantly, and the limiting oxygen index, tensile strength and tear strength data changed less significantly; it can be seen that the surface oxidation of the sole material in the present application can promote the improvement of its anti-slip performance.
[0144] Compared with Comparative Example 1, the modified filler in Comparative Example 2 uses coupling agent KH-550; the unsaturated monomer in Comparative Example 3 is replaced by hydroxyethyl methacrylate; the silicone rubber in Comparative Example 4 is prepared from aminopolydimethylsiloxane, isophorone diisocyanate, and 1,4-butanediol; its dry and wet friction coefficients, limiting oxygen index, tensile strength, and tear strength data deteriorate. It can be seen that the setting of the flame-retardant and anti-slip sole process and the components used therein of the present invention can promote the improvement of its flame retardancy, anti-slip performance, and mechanical properties.
[0145] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0146] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for producing a flame retardant anti-skid sole, characterized in that: Including the following processes: The rubber material, filler, plasticizer, foaming agent, zinc oxide, calcium carbonate and auxiliary materials are added to an open mill for plasticizing to obtain a mixed material; the mixed material is extruded and granulated through a single screw extruder to obtain a composite material; Through the injection molding machine, it is heated into a flat mold, vulcanized and foamed to obtain the sole material; the surface is oxidized to obtain a flame retardant and non-slip sole; The mixture includes the following components by mass: 100 parts of rubber material, 15-25 parts of filler, 10-15 parts of plasticizer, 2.5-3.2 parts of foaming agent, 1.2-5.0 parts of zinc oxide, 7-11 parts of calcium carbonate, and 4.5-8.0 parts of auxiliary materials; The rubber material comprises 50 to 60 parts of chlorinated polyethylene, 25 to 30 parts of ethylene-vinyl acetate copolymer, and 10 to 25 parts of silicone rubber; The silicone rubber is prepared by the following process: Mix ferrocene carboxylic acid, unsaturated monomer and 4-dimethylaminopyridine in anhydrous dichloromethane, cool to 0-3°C in a nitrogen atmosphere, and stir for 30-45 minutes; slowly add N,N'-dicyclohexylcarbodiimide within 60 minutes, and continue stirring for 60-75 minutes; restore the system temperature to room temperature, stir for 24 hours, and obtain ferrocene monomer; Mix bromoisobutyl silicone rubber, ferrocene monomer, N,N,N,N,N-pentamethyldiethyltriamine and anisole, add cuprous bromide under the protection of nitrogen atmosphere, heat to 90-95°C, react for 7-8h to obtain silicone rubber; The unsaturated monomer is prepared by the following process: Mix 2,2'-p-phenyl-bis(5-aminobenzoxazole) and a catalyst in dichloromethane, add phosphorus oxychloride under nitrogen atmosphere, stir for 5-8 minutes, add triethylamine, heat to 40-50°C, react for 6-7 hours, and obtain benzothiazole-phosphoryl dichloride; Mix benzothiazole-phosphoryl dichloride and butenediol in dichloromethane, raise the temperature to 40-50°C under nitrogen atmosphere, and reflux for 100-150 minutes to obtain an unsaturated monomer; The bromine-isobutyl silicone rubber is prepared by the following process: Mix amino polydimethylsiloxane and tetrahydrofuran, and slowly add diisocyanate under nitrogen atmosphere protection at 0-2°C, add within 30 minutes, and react for 8-9 hours; slowly add 2,2'-p-phenyl-bis(5-aminobenzoxazole), add within 30 minutes, and react for 90-120 minutes; add 1,4-butanediol, raise the temperature to 80-88°C, and continue to react for 4-5 hours to obtain hydroxy silicone rubber; Mix 2-bromoisobutyric acid and thionyl chloride in toluene, reflux for 30-60 minutes to obtain acid chloride, slowly add it to the tetrahydrofuran solution of hydroxy silicone rubber within 30 minutes, react for 8-12 hours to obtain bromoisobutyl silicone rubber; The filler is modified, and the specific modification process is: Under the protection of nitrogen atmosphere, ferrocenylimidate methyl ester and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane are mixed in anhydrous ethanol and stirred for 60 to 75 minutes; the temperature is raised to 80 to 100° C. and refluxed for 6 to 8 hours to obtain a coupling agent; The coupling agent, filler and ethanol solution are mixed, the temperature is raised to 58-62° C., and the reaction is carried out for 160-200 minutes to obtain a modified filler.
2. The process for manufacturing a flame retardant anti-skid sole according to claim 1, characterized in that: The process conditions of the surface oxidation are: the surface of the sole material is in contact with the oxide solution for 12 to 24 hours.
3. The process for manufacturing a flame retardant anti-skid sole according to claim 1, characterized in that: The filler is one of porous silicon powder, white carbon black, activated carbon, four-needle zinc oxide whisker and silicon carbide crystal.
4. The process for manufacturing a flame retardant anti-skid sole according to claim 1, characterized in that: The auxiliary materials include 1.0 to 1.6 parts of lubricant, 0.5 to 1.5 parts of antioxidant, 0.2 to 0.5 parts of anti-scorch agent, 1.6 to 2.0 parts of vulcanizing agent, and 1.2 to 2.4 parts of accelerator.
5. A flame retardant and anti-skid sole made according to the manufacturing process according to any one of claims 1 to 4.
Citation Information
Patent Citations
Antiskid wear-resistant foaming rain shoe sole and production process thereof
CN112980089A
Antiskid rubber sole and preparation method thereof
CN115368649A